2022
DOI: 10.1017/s1478951521002066
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth in palliative care patients and its associations with psychological distress and quality of life

Abstract: Objectives Posttraumatic growth (PTG) refers to positive psychological changes resulting from individuals’ inner struggles with traumatic events such as life-threatening illness. Although palliative care patients are confronted with their own mortality, little is known about their PTG experience. This study investigates whether PTG is an empirically relevant concept for palliative patients by assessing the prevalence and areas of growth, and examining associations with psychological distress and quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 60 publications
(76 reference statements)
1
15
0
1
Order By: Relevance
“…Others have reported high rates of PTG, especially in "appreciation of life" and "relating to others, " in a sample of parents in Portugal during the pandemic (78). An assessment of PTG in hospitalized patients undergoing bone marrow and/or stem cell transplantation and palliative care (79,80), found, as did our study, that "appreciation of life" was among the areas of most significant growth; the assessment also found no change in "personal strength." Finally, a study conducted by Holtmaat et al (81) on cancer patients that the most impacted domain was "relating to others.…”
Section: Discussionsupporting
confidence: 62%
“…Others have reported high rates of PTG, especially in "appreciation of life" and "relating to others, " in a sample of parents in Portugal during the pandemic (78). An assessment of PTG in hospitalized patients undergoing bone marrow and/or stem cell transplantation and palliative care (79,80), found, as did our study, that "appreciation of life" was among the areas of most significant growth; the assessment also found no change in "personal strength." Finally, a study conducted by Holtmaat et al (81) on cancer patients that the most impacted domain was "relating to others.…”
Section: Discussionsupporting
confidence: 62%
“…57 Thirteen studies only included people with terminal cancer diagnoses 31,32,4652,54,55,58,59 while four studies also included people with chronic heart failure, chronic obstructive airways disease and amyotrophic lateral sclerosis. 31,32,4452,5459 All quantitative studies used the Posttraumatic Growth Inventory (PTGI) to assess posttraumatic growth, while Mosher et al 55 and Wright et al 56 used a semi-structured questionnaire to gain qualitative data. A summary of included studies is found in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46]48,51,52,58 Higherlevelsofposttraumaticgrowthwerereportedbyyoungerpatients 45,59 and women. 45,47,57,59 Two studies found higher PTGI scores withparticipantsreportinggreatertimesincediagnosis/ timesincerecognitionofterminalillnessstatus, 31,59 while tworeportednodifference. 46,48 TwostudiesfromTangetal.…”
Section: Ptg Related Findingsmentioning
confidence: 99%
“…of physical functions, independence, sense of identity, and future, and to reflect on their own mortality [ 25 ]. These considerations prompted us to investigate gratitude in palliative care patients in an exploratory study, which found that gratitude was correlated with better quality of life, greater posttraumatic growth, and less psychological distress [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%